Pengaruh Lahan Berkontur pada Penataan Massa Hotel Golden Tulip Resort - Ikaprasi, Fransiska Oktiviani Chrisillia; Winasi, Sri Suryani Yuprapti (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Batu City is one of the cities in East Java that has a wealth of tourism so it is not surprising that many accommodation buildings such as villas, hotels, and resorts stand on uneven surfaces because most of the Batu city contours have a slope of 25-40% to more than 40%. The purpose of this research is to find out the planning of the mass arrangement of resort hotels, the influencing aspects, and the ways in which development risks on contoured land can be overcome for the convenience and resilience of the building area. The research method used is descriptive, and data is collected through observation, documentation, and literature study. The object of this research is the Golden Tulip Resort Hotel in Batu City. The results of this study are that the mass arrangement in the building area is influenced by the slope of the land or topography on the site and the achievement of circulation. The placement of the building mass is arranged according to the different elevations on the land and the zone's needs. Although it has contours on the land, the design response given, such as stairs connecting each building, succeeds in providing visitors with comfort in accessing its achievements.